Virtual metrology frame technique for improving dynamic performance of a small size machine tool - Abir, Jonathan; Longo, Stefano; Morantz, Paul; Shore, Paul (Elsevier, 2016)
This paper presents a novel concept, a virtual metrology frame, for enhancing the dynamic performance of a machine tool with a flexible structural frame. The dynamic properties of a machine are directly affected by the stiffness of its frame, and its reference system; thus, by having an unstressed metrology frame, superior dynamic capabilities can be achieved. The developed concept does not require physical components associated with metrology frame; hence it is ideal for machine tools with requirements for small footprint and ultra-precision performance. The concept relies on an accelerometer based dynamic displacement feedback technique, where the accelerometer is used as a precision frame displacement sensor. The concept does not require a complex controller, and was realized in an off-the-shelf CNC controller. The concept was demonstrated on a linear motion system, a simplified version of a compact size CNC machine, and its servo bandwidth and dynamic stiffness were improved by 36% and 70% respectively, which are the key parameters for improving the machining accuracy.
Keywords: Acceleration based displacement; Flexible frame; PID controller; Sensitivity function; Virtual metrology frame